The Integration of the Qur’an and Ḥikmah in the Thought of Majid Irsan al-Kailani Philosophical Foundations and Implications for the Pesantren Curriculum - Samsirin, Samsirin; Arif, Mahmud; Karwadi, Karwadi (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2025)
This study examines the integration of al-Kitāb (scriptural knowledge) and al-Ḥikmah (wisdom-based education) in the educational philosophy of Majid Irsan al-Kilani and its relevance to the pesantren curriculum in Indonesia. The integration of revelation and reason has become increasingly urgent in response to contemporary challenges in Islamic education, including the dichotomy between religious and secular sciences, moral fragmentation, and the loss of epistemological coherence. Al-Kilani proposes a holistic curricular paradigm that unites divine guidance with rational inquiry and ethical formation. Using a qualitative library research approach, this study analyzes classical Islamic sources and modern educational theories to explore how pesantren can operationalize this integrative framework. The findings show that pesantren, with their epistemological foundations in kitab kuning, character formation, experiential learning, and spiritual mentorship, possess strong structural and cultural capital to implement such integration. The proposed curriculum model consists of three progressive levels that combine jurisprudence, logic, and ethics while cultivating intellectual depth and spiritual maturity. Strengthened by systematic evaluation and guided by holistic educators (rabbānīyūn), pesantren can effectively address contemporary educational fragmentation through an integrated vision of knowledge.